Characteristics of heat insulating clay bricks made from zeolite, waste steel slag and expanded perlite. Issue 7 (May 2018) - Farnood Ahmadi, Pedram; Ardeshir, Abdollah; Ramezanianpour, Amir Mohammad; Bayat, Hamid
Abstract: In order to lessen the energy loss of buildings during the operation phase, and also considering the importance of sustainable construction, producing bricks having more desirable thermal characteristics has become essential. In this study, insulation bricks composed of expanded perlite (EP), natural zeolite, ground granulated blast furnace slag (GGBFS) and clay were fabricated. The effect of replacing clay with GGBFS, zeolite and EP in amounts up to 15%, 15%, and 50% respectively on the bricks' properties was investigated. Mix proportion parameters of bricks were analyzed using the Taguchi method. Various properties of bricks including density, weight loss, shrinkage, apparent porosity, water absorption, resistance to freezing and thawing, compressive strength, thermal conductivity, and microstructural analysis of fired bricks were examined and compared against standard requirements for bricks. Overall, the results showed that while satisfying the standard requirements, bricks containing the aforementioned additives had lower thermal conductivity compared to normal bricks, and therefore, they could be utilized as heat insulation materials.